2007
DOI: 10.1302/0301-620x.89b2.18057
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for developmental dysplasia of the hip using the Pavlik harness

Abstract: We reviewed the medical records of 115 patients with 130 hips with developmental dysplasia with complete dislocation in the absence of a neuromuscular disorder, spontaneous reduction with a Pavlik harness, and a minimum of 14 years' follow-up. The mean age at the time of harness application was 4.8 months (1 to 12) and the mean time spent in the harness was 6.1 months (3 to 12). A total of 108 hips (83.1%) were treated with the harness alone and supplementary surgery for residual acetabular dysplasia, as defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 39 publications
4
74
0
6
Order By: Relevance
“…Twenty-two hips required supplementary surgery for residual dysplasia, the choice of surgery depending on the state of joint and surgeon's preference. A satisfactory outcome (Severin classes I and II) was achieved in 119 patients [47] .…”
Section: Treatment Of a Child (One To Six Months)mentioning
confidence: 89%
“…Twenty-two hips required supplementary surgery for residual dysplasia, the choice of surgery depending on the state of joint and surgeon's preference. A satisfactory outcome (Severin classes I and II) was achieved in 119 patients [47] .…”
Section: Treatment Of a Child (One To Six Months)mentioning
confidence: 89%
“…Sibinski et al [19] noted that residual acetabular dysplasia was more common if DDH was complicated by osteonecrosis. Nakamura et al [14] reported on 130 hips with DDH. For patients who did not have osteonecrosis develop, 97% had Severin Grade I or II hips at 14 years, with only 44% Grade I or II hips in patients with osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Поражение зон роста прок-симального отдела бедренной кости у ребенка вследствие ишемии или некроза в тазобедренном суставе приводит к укорочению шейки и конеч-ности в целом, многоплоскостным деформациям проксимального отдела бедра. Это обусловливает развитие раннего деформирующего артроза тазо-бедренного сустава и резко ухудшает прогноз за-болевания [3,5,25,36,38]. В наших наблюдениях основными причинами развития АНГБК при консервативном лечении детей с врожденным вывихом бедра являлись: -отсутствие предрепозиционной подготовки; -одномоментные попытки закрытого вправле-ния бедра; -фиксация в ортопедической конструкции при избыточном отведении в тазобедренных су-ставах, близком к 90 градусам [37,39]; -длительная фиксация в ортопедических кон-струкциях при отсутствии вправления голов-ки бедра; -многократные попытки закрытого вправления бедра.…”
Section: диагностика и лечение в период 3-6 месunclassified
“…Важным аспектом проблемы являются вопро-сы дифференциальной диагностики заболевания, а именно раннее выявление вывихов бедра недис-пластической природы [38,42,43].…”
Section: диагностика и лечение в возрасте 6-12 месunclassified